Quantitative comparison between carotid plaque hardness and histopathological findings: an observational study - Daisuke Fukushima; Kosuke Kondo; Naoyuki Harada; Sayaka Terazono; Kei Uchino; Kazutoshi Shibuya; Nobuo Sugo (BMC, 2022)
Abstract Background Plaque hardness in carotid artery stenosis correlates with cerebral infarction. This study aimed to quantitatively compare plaque hardness with histopathological findings and identify the pathological factors involved in plaque hardness. Methods This study included 84 patients (89 lesions) undergoing carotid endarterectomy (CEA) at our institution. Plaque hardness was quantitatively measured immediately after excision using a hardness meter. Collagen and calcification were evaluated as the pathological factors. Collagen was stained with Elastica van Gieson stain, converted to a gray-scale image, and displayed in a 256-step histogram. The median gray-scale median (GSM) was used as the collagen content. The degree of calcification was defined by the hematoxylin-eosin stain as follows: "0:" no calcification, "1:" scattered microcalcification, or "2:" calcification greater than 1 mm or more than 2% of the total calcification. Carotid echocardiographic findings, specifically echoluminance or the brightness of the narrowest lesion of the plaque, classified as hypo-, iso-, or hyper-echoic by comparison with the intima-media complex surrounding the plaque, and clinical data were reviewed. Results Plaque hardness was significantly negatively correlated with GSM [Spearman's correlation coefficient: -0.7137 (p < 0.0001)]: the harder the plaque, the higher the collagen content. There were significant differences between plaque hardness and degree of calcification between "0" and "2" (p = 0.0206). For plaque hardness and echoluminance (hypo-iso-hyper), significant differences were found between hypo-iso (p = 0.0220), hypo-hyper (p = 0.0006), and iso-hyper (p = 0.0015): the harder the plaque, the higher the luminance. In single regression analysis, GSM, sex, and diabetes mellitus were significant variables, and in multiple regression analysis, only GSM was extracted as a significant variable. Conclusions Plaque hardness was associated with a higher amount of collagen, which is the main component of the fibrous cap. Greater plaque hardness was associated with increased plaque stability. The degree of calcification may also be associated with plaque hardness.